Rancang Bangun Pembersih Filter Oli Turbin Uap Unit 015-T05 A - Kurniawan, Dafa Rizki; Felixtianus Eko Wismo; Sugiyanto; Harjono (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The oil filter plays a very important role in the lubrication system, where the oil filter functions as the main filter for the lubrication system. Companies that operate in the energy conversion sector use machines that operate 24 hours to produce their products. The steam turbine engine is a very influential tool. Where this tool is the driver of the pumps that distribute pressurized liquid fluid from the medium pressure process to high pressure. However, this machine has a problem, namely the engine's lubrication system is less than optimal, which is caused by manually cleaning the oil filter. The manual oil cleaning process apparently did not comply with the recommendations in the filter manufacturer's manual. Based on these problems, researchers created a design for a steam turbine unit 015-T05 A oil filter cleaner with a backwash system aimed at simplifying the oil filter cleaning process. The method used in the design of this tool is the process of basic design concepts, calculating the nozzle used, and producing the design results. Based on this method, the research produces a design that is in accordance with the specified design design. This tool was tested using three variations of cleaning fluid, namely Pertamax, thinner and methanol. Testing this tool also uses gas fluid output from the compressor with variations of 4 bar and 6.2 bar. In conclusion, this tool is able to clean the oil filter optimally, with a cleaning pressure of 6.2 bar, this tool is able to increase the cleanliness indicator of a dirty oil filter. As a result, the oil filter that was cleaned with Pertamax gasoline obtained a cleanliness value of 5.8 bar, the most optimal indicator, and was able to increase the filter's performance time by 720 hours.